Clinical and epidemiological study of leprosy cases in the University Hospital of Brasília: 20 years - 1985 to 2005 Estudo clínico-epidemiológico dos casos de hanseníase do Hospital Universitário de Brasília: 20 anos - 1985 a 2005 - Gerson Oliveira Penna; Ana Maria Pinheiro; Lucas Souza Carmo Nogueira; Luciana Rabelo de Carvalho; Marcela Bahia Barretto de Oliveira; Verena Portela Carreiro (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
Hansen's disease, also known as leprosy, is an infectious disease still prevalent in Brazil. It is a chronic illness with acute immunological phenomena known as leprosy reactions. In the Federal District of Brazil, the University Hospital of Brasília is the reference centre for leprosy care. The study aimed to characterize the clinical and epidemiological profile of Hansen's disease patients at the University Hospital of Brasília, by descriptive, retrospective analysis of 1,124 patients over the period from 1985 to 2005. The pattern of leprosy in this study demonstrated that type 2 leprosy reactions were common, especially in the lepromatous form and presented a direct correlation with the bacilloscopic index. The prevalence and frequency of severe complications, such as leprosy reactions, emphasize the importance of the ongoing study of leprosy and the need for continual improvement in the scope of knowledge concerning its treatment. Hanseníase, também conhecida como lepra, é doença infecciosa prevalente no Brasil. Caracteriza-se por curso crônico, com fenômenos imunológicos agudos denominados episódios reacionais. No Distrito Federal, o Hospital Universitário de Brasília é referência na assistência da hanseníase. O objetivo do estudo foi caracterizar o perfil clínico-epidemiológico dos doentes portadores de hanseníase do Hospital Universitário de Brasília. Foi realizada análise descritiva e retrospectiva de 1124 doentes portadores de hanseníase no período de 1985 a 2005. O padrão da hanseníase no nosso estudo concretizou-se por apresentar maior prevalência de reações do tipo 2, especialmente na forma lepromatosa e correlacionando-se diretamente com o índice baciloscópico. A significativa prevalência e freqüência de complicações graves como os episódios reacionais ressaltam a importância do estudo da doença e a necessidade de aprimoramento contínuo dos conhecimentos sobre a mesma.